HUBUNGAN ANTARA FAKTOR PENGETAHUAN, KETERSEDIAAN FASILITAS DAN DUKUNGAN TENAGA KESEHATAN TERHADAP PENERAPAN KEBIASAAN CUCI TANGAN PAKAI SABUN PADA MASYARAKAT DI WILAYAH KELURAHAN SUKAMAJU BARU TAHUN 2022 - Nathasya Echa Indriani; Nur Rizky Ramadhani; Nina Nina (Jurnal Kesehatan Masyarakat, 2023)
Handwashing with soap (CTPS) is a way to remove dirt and dust from both hands with water and soap. CTPS is very useful for preventing various diseases that cause death, for example Diarrhea and Upper Respiratory Tract Infection which are very often the cause of death in children. In addition, there are also several diseases caused by the lack of habit of washing hands with soap such as Hepatitis, Covid-19, Skin and Eyes. This study aims to determine the relationship between knowledge factors, availability of facilities and support from health workers to the implementation of handwashing habits with soap in the region of sukamaju baru in 2022. This research method is descriptive quantitative using a cross sectional design. The sampling technique in this study was simple random sampling and 67 samples were obtained. The data used is primary data disseminated through online questionnaires. Data analysis was carried out univariately and bivariately using the Chi-square test. Based on statistical tests, there is 1 variable that shows a relationship, namely Knowledge with p-value = 0.010 (p<0.05) with OR = 0.240, while there are two variables that show no relationship, namely the availability of facilities with p-value = 0.417 (p>0.05) and health worker support with p-value = 0.135 (p>0.05). Based on the results of the study, it is hoped that the puskesmas with the Sukamaju Baru Village together with community leaders can work together to increase community knowledge in Sukamaju Baru Village by holding counseling and monitoring evenly in each RW so that more and more people have good knowledge and habits, especially in maintaining personal hygiene and health.